Aberrant expression of selenium-containing glutathione peroxidases in clear cell renal cell carcinomas - Rudenko, E.; Kondratov, O.; Gerashchenko, G.; Lapska, Y.; Kravchenko, S.; Koliada, O.; Vozianov, S.; Zgonnyk, Y.; Kashuba, V. (Experimental Oncology, 2015)
Aim: To find putative diagnostic markers for clear cell renal cell carcinomas (ccRCC). Material and methods: Quantitative polymerase chain reaction (Q-PCR), bisulfite treatment, methylation-specific PCR, analysis on cBioPortal for Cancer Genomics. Results: We have found that expression of GPX 1, GPX3, and GPX4 genes was decreased in ccRCC. We have shown that the number of alanine (GCG) repeats at the amino terminus of the GPX1 protein is variable. It was reported earlier that an allele that possess 5 alanine repeats is associated with the increased cancer risk. According to the obtained data, the allele with the 5 alanine repeats was also present in a group of healthy donors. Moreover, the frequency of alleles with repeats was similar among ccRCC patients and healthy individuals. We found that decreased expression of GPXs genes was not associated with promoter methylation. To provide other explanation, an analysis on the gene copy number was performed. We have found the heterozygous deletions for GPX1 gene, amplification for GPX3 gene, and no change in gene copy number for GPX4. Conclusions: Our data support the hypothesis that GPX1, GPX3, and GPX4 genes may play a role in ccRCC cancerogenesis and therefore they might be considered as putative diagnostic markers for ccRCC. Key Words: clear cell renal cell carcinomas, selenium-containing GPXs, genetic and epigenetic regulation.